Post-Traumatic Stress Disorder: Ethical and Legal Relevance to the Criminal Justice System. Issue 2 (2014) - Soltis, Kathryn; Acierno, Ron; Gros, Daniel F.; Yoder, Matthew; Tuerk, Peter W.
Abstract : New coverage of the recent wars in Afghanistan and Iraq, and the ensuing public education campaigns by the Department of Veterans Affairs and private veterans advocacy groups combine to call the public's attention to the many potential mental health problems associated with traumatic event exposure. Indeed, since 2001, Operation Iraqi Freedom (OIF) and Operation Enduring Freedom (OEF) combat and peacekeeping missions have been characterized by high levels of exposure to acts of extreme violence, with often gruesome effects. Less publically discussed is the fact that a surprisingly large number of United States civilians also report exposure to traumatic events, such as severe interpersonal violence, natural disasters, and serious automobile accidents. In fact, approximately 70% of randomly sampled respondents indicated that they have experienced an incident characterized by significant perceived life threat at some point during their lives.